The Effect of Diabetic Foot Exercises on Ankle Brachial Index Values and the Degree of Diabetic Foot Risk in Diabetes Melitus Patients: Pengaruh Senam Kaki Diabetik terhadap Nilai Ankle Brachial Indeks dan Derajat Risiko Kaki Diabetik pada Pasien Diabetes Melitus - Nurmalisa, Baiq Emy; supirno, Supirno (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Background: The prevalence of Diabetic Foot Ulcers (DFU) in diabetics is 4-10% where this condition more often affects the elderly. DFU is a serious marker of a disease that if optimal prevention is not carried out from the start, the wound deteriorates rapidly, and the worst is amputation. Diabetic foot exercises are used as leg exercises and are beneficial in reducing pain, reducing nerve damage, controlling blood sugar and increasing blood circulation in the feet. The purpose of this study was to analyze the effect of diabetic foot exercise on the degree of risk of diabetic foot ulcers and the Ankle brachial index value in Diabetes Mellitus patients in the Work Area of the Mamboro Health Center. Methods: This type of research is quasi-experimental with a one group pretest posttest design. The sample is 16 people. The instruments used were a monofilament test, sphygmomanometer, stethoscope, and an instrument for assessing the risk of diabetic foot. Data analysis used is paired t test and Wilcoxon test. Results The results showed that diabetic foot exercise had an effect on changes in the value of blood circulation (ABI) with a p value (0.000) and a score of degrees of risk of diabetic foot with a p value (0.001). Conclusion of this study is that diabetic foot exercise has a statistical effect on both the ABI value and the diabetic foot degree score. Suggestions from this study are that nurses more often conduct DM foot exercise education in an effort to prevent DFU